The trade-off between corporate social responsibility and competitive advantage: a biform game model - Zhao, Xiaoyang; Tan, Justin; Zhong, Shuxin (Technological and Economic Development of Economy, 2022)
This paper uses a biform game model to study firms’ trade-offs between corporate social responsibility (CSR) and competitive advantage. We focus on the context in which a competitive advantage may lead to a non-profitable scenario. It is possible that the first mover’s investment in competitive strength may deter itself from the market, which encourages firms’ investment in CSR over competitive strength. As a result, in some circumstances, firms may actively choose a CSR strategy over a competitive strategy. Our results show that (1) technological characteristics, (2) industrial structure, and (3) institutional environments are factors that influence the rational equilibrium of our model and the balance between competitive advantage and CSR. The mechanism and boundary on how firms make trade-offs between CSR activities and competitive strength are exhibited by our model, which provides a framework for decision-making and adds new insights into the strategic balance between market and non-market strategies. First published online 10 February 2022